The Critique of Arab Thought: Mohammed Arkoun's Deconstruction Method - Soekarba, Siti Rohmah (Makara Human Behavior Studies in Asia, 2006)
Mohammed Arkoun is one of international modern Islamic thinkers that his thought comes into Islamic thinking discourses in Indonesia recently. His Islamic thought was influenced by the modern philosophical concepts such as ‘myths’ of Ricouer, postmodern concepts like ‘discourse’ and ‘episteme’, which were developed by Foucault as well as ‘deconstruction’ of Derrida. If Derrida focused on deconstruction as a final concept, on the other hand Arkoun insisted that ‘deconstruction’ must be followed by ‘reconstruction’ of a discourse. Arkoun’s reconstruction leaves the limitation, the rigidity and deviation from the past. Arkoun proposes two ways: firstly it is ‘ijtihad’ and subsequently it is Islamic critical reason with the whole of critical meaning. In this research I used the method of library investigation. Based on the result I came into the conclusion that Arkoun loss the communication with the scholars in the Islamic world, particularly in the Middle East tradition. Since, he applied the method of deconstruction that Islamic world percept it was going too far.